Empathic Teaching Practices in Enhancing Intrinsic Motivation among Students from Non-Intact Families: A Qualitative Case Study - Yadi Budiman; Khaerul Syobar; Neneng Tripuspita (Educenter : Jurnal Ilmiah Pendidikan, 2026)
Students from non-intact families often experience socio-emotional challenges that affect their academic engagement and motivation. This study aims to explore empathic teaching practices and their role in fostering intrinsic motivation among students from non-intact families in social studies learning. A qualitative case study design was employed involving 3 social studies teachers and 12 students at SMP Negeri 3 Paseh, Indonesia. Data were collected through semi-structured interviews, classroom observations (four sessions), and document analysis. The data were analyzed using thematic analysis involving open coding, axial coding, and selective coding. The findings reveal four major themes: (1) teachers’ awareness of students’ socio-emotional conditions, (2) empathic classroom practices, (3) instructional strategies fostering intrinsic motivation, and (4) positive impacts on student engagement and confidence. Empathic teaching practices, such as supportive communication and individualized approaches, significantly contributed to students’ intrinsic motivation and classroom participation. This study contributes to extending Self-Determination Theory in vulnerable student contexts and offers practical pedagogical implications for inclusive education.